Column Test Model of Expansive Soil Stabilized with Lime Injection Using Shallow Mixing Method - D. B. Pinasang, T. Harianto, A. B. Muhiddin, A. A. Amiruddin, (Design Engineering, 2022)
The purpose of this study was to develop a prototype of an expansive soil pile column with lime stabilization using the shallow mixing method. The design of the shallow mixing device model and the methodology for stabilizing the expansive soil layer at shallow depths are part of the research that focuses on evaluating the effectiveness of the lime column in reducing the swelling and shrinking potential of the expansive soil modeled in the test box. Expansive soil lime column modeling as many as 4 columns with a column diameter of 10 cm and the distance between 2D columns with a column height of 1 meter. The volume of quenched lime (Ca (OH)2) is 200 kg/m3 of dry soil weight, the water-lime ratio is 1.2 and the curing time is 7 days. The test results show that the development can be reduced by 43.2% compared to the soil without improvement. This study shows that shallow mixing technology is a viable option for stabilizing expansive soils.